Bridging Spatial Inequality Through Infrastructure: A Sociological Study on Sustainable Development of Small Island Communities in Eastern Indonesia - Ony Frengky Rumihin (Baileo: Jurnal Sosial Humaniora, 2026)
Spatial inequality between central regions and small islands in Eastern Indonesia shows that infrastructure development remains uneven and socially unjust. This study aims to analyze the role of infrastructure in reducing spatial and social inequality in small island regions, identify sociocultural dynamics influencing infrastructure acceptance and sustainability, and formulate a community-based model of sustainable development. Using a qualitative sociological approach, the study employs SWOT and Participatory Planning Analyses to examine strengths, weaknesses, opportunities, and threats from a local-social perspective, combined with Participatory Rural Appraisal (PRA) through in-depth interviews, field observations, and focus group discussions in Metimiarang Island. Findings indicate that infrastructure serves as a social integrator that enhances access to basic services, economic opportunities, and social cohesion in peripheral areas. Yet, weak governance, fragmented stakeholder coordination, and low community participation hinder effectiveness. Sustainable programs are those integrating local wisdom and social institutions, notably community-based 3R (reduce, reuse, recycle) systems. The study’s novelty lies in introducing a socio-infrastructural bridging framework, positioning infrastructure as a social bridge linking marginalized regions to development centers. Theoretically, this research expands development sociology by embedding spatial and ecological dimensions, reinforcing the relevance of the sociology of infrastructure within the Sustainable Development Goals, particularly Goals 9 (Industry, Innovation, and Infrastructure) and 11 (Sustainable Cities and Communities).